2008
DOI: 10.1051/gse:2008013
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mapping, differential origin and evolution of theS100gene family

Abstract: -S100 proteins are calcium-binding proteins, which exist only in vertebrates and which constitute a large protein family. The origin and evolution of the S100 family in vertebrate lineages remain a challenge. Here, we examined the synteny conservation of mammalian S100A genes by analysing the sequence of available vertebrate S100 genes in databases. Five S100A gene members, unknown previously, were identified by chromosome mapping analysis. Mammalian S100A genes are duplicated and clustered on a single chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The other genes belonging to the subfamilies of S100B, S100P, S100Z and S100G are, respectively, located at chromosome loci 21q22, 4p16, 5q14 and Xp22. It was been reported that S100A genes had a common origin in the molecular evolution while S100B, of S100P, S100Z and S100G had different origins, so S100A genes might have a universal conserved regulatory sequences [35]. Given their highly conserved Gli1 binding homologous sequences, it is speculated that they play similar role related to Gil1, though we cannot exclude the possibility that they have different functions unrelated to Gil1.…”
Section: Discussionmentioning
confidence: 86%
“…The other genes belonging to the subfamilies of S100B, S100P, S100Z and S100G are, respectively, located at chromosome loci 21q22, 4p16, 5q14 and Xp22. It was been reported that S100A genes had a common origin in the molecular evolution while S100B, of S100P, S100Z and S100G had different origins, so S100A genes might have a universal conserved regulatory sequences [35]. Given their highly conserved Gli1 binding homologous sequences, it is speculated that they play similar role related to Gil1, though we cannot exclude the possibility that they have different functions unrelated to Gil1.…”
Section: Discussionmentioning
confidence: 86%
“…The carboxyl–terminal (c-terminus) EF-hand domain is referred to as the conical (higher affinity) calcium binding loop that encompasses 12 amino acids, whereas the low affinity N-terminal loop formed of 14 amino acids is known as the “pseudo” or S100-specific EF–hand domain [3, 4]. In humans, most S100 genes are clustered at chromosomal locus 1q21 except S100B, S100p and S100Z, which are mapped at chromosome 12q22, 4 and 5 [58]. Members of the S100 protein family have sequence homology between 22 to 57% with marked variance at the hinge region and C-terminus, which is thought to contribute to the diversity in their biological function [6].…”
Section: S100 Family Of Proteinsmentioning
confidence: 99%
“…Phylogenetically, these proteins appear to be a young group present only in vertebrates (Shang et al 2008). Interestingly, most of the genes coding for S100 proteins are localized in a cluster on human chromosome 1q21, mouse chromosome 3f2 (Schafer et al 1995; Ridinger et al 1998), and chromosome 2q34 in the rat (Ravasi et al 2004).…”
Section: The S100 Proteinsmentioning
confidence: 99%